Cinema e sexualidade na república de Weimar: A “Nova Mulher” no filme A Caixa de Pandora (1929) - Nunes, Vitória Gondim Real (2024)
The Weimar Republic (1918-1933) experienced significant changes, including the emergence of the “New Woman”, which generated social anxieties about traditional gender roles. As a consequence, a growing misogynistic discourse placed the “New Woman” as responsible for the country's social, political, economic and cultural crisis. Weimar cinema, in this context, also contributed to affirm or deny many of these discourses, and several films from that time can be read either as part of social mechanisms of gender normalization, or as questioning these models. In this way, the work aims to undertake an analysis of the film Pandora's Box (1929), by G. W. Pabst, to understand the ways in which the film transcodes the discourses of the Weimar Republic on gender and sexuality, using Cultural Studies as a methodology. As a partial result, the project understands that the representation in the film of the sexuality of the “New Woman” can be interpreted both as emancipated and as decadent.